Assessing Olympic legacy claims: Evaluating explanations of causal mechanisms and policy outcomes. (July 2020) - Chen, Shushu; Henry, Ian
Olympic impact/legacy analysis as a research area has become a frequently discussed topic in the sociology of sport literature in general and in event management in particular since the 2000s. Although Olympic impact/legacy analysis has increased in volume, many studies still face methodological challenges (e.g. failure to adopt rigorous theoretical frameworks or overlooking additionality). The aim of this article is to unpack the logic of stakeholders in a critical evaluation of two London 2012 legacy programmes, critically reviewing the outcomes sought, and the actions adopted to achieve those outcomes, with reference to the concepts of programme theory, action theory and process tracing. We seek to redress the shortcomings of previous Olympic legacy claims which have failed to link theoretically informed accounts of the nature of Olympic-led/Olympic-inspired outcomes to explanations of the specific causal mechanisms that account for the generation of such outcomes.